Microbial and immunological investigations of chronic non-ulcerative blepharitis and meibomianitis. Issue 8 (August 1985) - Seal, D V; McGill, J I; Jacobs, P; Liakos, G M; Goulding, N J
Abstract : Concentrations of tear lysozyme, lactoferrin, ceruloplasmin, IgG, and IgA have been measured by enzyme linked immunosorbent assay (ELISA) in patients with chronic non-ulcerative blepharitis and meibomianitis at the same time as the lid and conjunctivae were cultured for bacteria and fungi by a semiquantitative method. A group of normal controls aged 20 to 80 were similarly sampled, when strains of Staphylococcus epidermidis from their eyes and the patients' eyes were biotyped according to Baird-Parker's scheme. 5% of blepharitis cases had increased numbers of Staph. aureus present on the lids, compared with only a scanty growth obtained from 5% of normals. 7% of blepharitis cases had increased numbers of Staph. epidermidis type VI (coagulase-negative, mannitol-fermenting) present compared with a scanty growth obtained from 6% of normals. Isolation rates of other types of Staph. epidermidis did not differ from those in normals; no types were associated with meibomianitis. Tear protein profiles were normal in most patients, and there was no increase in tear IgA or IgG, which is expected with chronic infection. Overall our evidence suggests that in 88% of cases these lid conditions have an inflammatory aetiology not associated with infection. Staphylococcal isolates often found in the eye usually represent a normal commensal rather than pathogenic flora.